MON-LB76 Impact of Age on Survival and Prognostic Factors in Radioiodine Refractory Differentiated Thyroid Cancer Patients - Buffet, Camille (J Endocr Soc, 2020)
BACKGROUND Age has been identified as a major prognostic factor in differentiated thyroid cancer (DTC). Prognostic factors of radioiodine-refractory differentiated thyroid cancer (RAIR-DTC) are poorly described. The objectives of our study were to analyze the influence of age on the survival of patients with RAIR-DTC and to determine their prognostic factors according to age. PATIENTS AND METHOD This single centre, retrospective study enrolled 155 patients diagnosed with a RAIR-DTC between 1991 and 2017. The primary end point was overall survival (OS). Secondary endpoints were progression free survival (PFS) and prognostic factors. RESULTS Median OS was 8.2 years (95% IC: 5.3-9.6). There was no difference according to age (P = 0.47) with median OS at 8.3 years in patients < 65 (95% IC: 4.9-10), and 7.5 years in patients > 65 (IC: 4,9-11,3). PFS after RAIR-diagnosis was 2.1 years (95% IC: 0.8-3) in patients < 65, and 1 year in patients > 65 (95% IC: 0.34-0.68). In both groups, progressive disease despite 131I reduced OS, in comparison with other RAIR criteria. In patients < 65, an interval between the initial diagnosis of DTC and the diagnosis of RAIR metastatic disease more than 3 years was protective from poor OS (HR: 2.12; 95% CI: 1.05-4.27). In patients > 65, presence of a mediastinum metastasis at RAIR-diagnosis was a significant factor for decreased OS (HR: 0.22; 95% CI: 0.11-0.44). No difference was found between groups regarding therapeutic management. One third of patients received tyrosine kinase inhibitors in both groups (< 65 years: 20 patients (28%), ≥ 65 years: 28 (33%), P = 0.49). They were also similar regarding the number of lines received or the median duration of treatment (< 65 years: 19.5 months (2-59), ≥ 65 years: 19 months (1-64), p= 0.35). At least one line of TKI was transitorily or definitively withdrawn due to toxicity in 40% of patients (< 65 years: 8/20 patients (40%), ≥ 65 years: 13/28 (46%), p= 0,037). CONCLUSION In RAIR-DTC patients, age was not predictive of the outcome. In our study, older patients seem to have benefited from intensive therapeutic management. Continual progress made in the management of RAIR-DTC, especially with the implementation of systemic therapies should probably make reconsider the natural history and conventional prognostic factors of RAIR-DTC.